2022
DOI: 10.1002/ptr.7658
|View full text |Cite
|
Sign up to set email alerts
|

Curculigoside rescues hippocampal synaptic deficits elicited by PTSD through activating cAMP‐PKA signaling

Abstract: Chronic traumatic stress results in various psychiatric disorders, especially posttraumatic stress disorder (PTSD). Previous study demonstrated that curculigoside (CUR) a component of Rhizoma Curculiginis prevented fear extinction and stress‐induced depression‐like behaviors. However, its effects on PTSD and the mechanisms are still not completely clear. In this study, we observed typical PTSD‐like phenotypes, synaptic deficit, and reduction of BDNF/TrkB signaling pathway in mice receiving modified single prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…60 Meanwhile, activation of the cAMP-PKA signalling pathway has been found to rescue hippocampal synaptic defects caused by posttraumatic stress disorder (PTSD). 61 In this study, we found that Prkaca was markedly downregulated in OGD/R-induced neurons and MCAO/R rats.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…60 Meanwhile, activation of the cAMP-PKA signalling pathway has been found to rescue hippocampal synaptic defects caused by posttraumatic stress disorder (PTSD). 61 In this study, we found that Prkaca was markedly downregulated in OGD/R-induced neurons and MCAO/R rats.…”
Section: Discussionmentioning
confidence: 54%
“… 60 Meanwhile, activation of the cAMP‐PKA signalling pathway has been found to rescue hippocampal synaptic defects caused by posttraumatic stress disorder (PTSD). 61 In this study, we found that Prkaca was markedly downregulated in OGD/R‐induced neurons and MCAO/R rats. Overexpression of Prkaca reduced secretion of inflammatory factors and inhibited OGD/R‐induced Ca 2+ overload and neuronal apoptosis through activating the cAMP/PKA‐MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Among them, many researchers show high concern about CREB/BDNF/TrkB signaling in depression. Through the same signaling pathway, these studies provide many meaningful ideas for the exploration of depression like myelination, hippocampal synaptic plasticity, and G protein-coupled receptor 39, which have something in common with our research.…”
Section: Discussionmentioning
confidence: 84%
“…In antidepressant drug treatment, most drugs are metabolized via the polymorphic cytochrome P450 enzyme CYP2D6 55 . Activating cAMP-PKA signaling could prevent the behavioral changes and hippocampal synaptic deficits elicited by posttraumatic stress disorder (PTSD) 56 . Restoring hippocampal cAMP and BDNF levels could be an antidepressant treatment 57 .…”
Section: Discussionmentioning
confidence: 99%